Attention Mechanism Cloud Detection With Modified FCN for Infrared Remote Sensing Images - Liyuan Li (IEEE, 2021)
Semantic segmentation (SS) has been widely applied for cloud detection (CD) in remote sensing images (RSIs) with high spatial and spectral resolution because of its effective pixel-level feature extraction structure. However, the typical model of lightweight SS, namely the fully convolutional network (FCN) with only seven layers, has difficulty in extracting high-level features, and the heavy pyramid scene parsing network (PSPNet) with complicated calculations is not practical in real-time CD, let alone on-orbit CD. So, in view of the problems above, we propose a compact attention mechanism cloud detection network (AM-CDN) based on the modified FCN to refine and fuse the multi-scale features for on-orbit CD. Specifically, taking the FCN as the baseline, our model increases the numbers of hidden layers and adds the residual connections between the input and output to eliminate the network degradation and extract the advanced context feature maps effectively. To expand the receptive field without losing the spatial information, the ordinary convolutions in FCN are replaced by the dilated convolution in AM-CDN. And inspired by the selective kernels of human vision, we introduce the convolutional attention mechanism (AM) into the encoder to adaptively adjust the receptive field to highlight the key texture features. According to experimental results using Landsat-8 infrared RSIs, the accuracy of the proposed CD method is 95.31%, which is 10.17% higher than that of FCN. And the calculation complexity of AM-CDN is only 7.63% of that of PSPNet.